2017
DOI: 10.1002/ajcp.12206
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Having a Little Struggle With This, Can You Help Me Out?”: Examining Impacts and Processes of a Social Capital Intervention for First‐Generation College Students

Abstract: Social capital plays a key role in college and career success, and research indicates that a dearth of on-campus connections contributes to challenges first-generation college students face in effectively navigating the college environment. This study investigates a novel intervention that focuses on the development of skills and attitudes to empower first-generation college students to cultivate social capital and on-campus connections during the transition to college. A mixed methods, explanatory design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 44 publications
0
125
1
1
Order By: Relevance
“…Using a combination of co‐curricular instruction, group activities and experiential assignments, participants can be oriented to explore their new social and academic environment, purposely looking into recruiting a diverse group of individuals (e.g., advanced peers, faculty, and university staff) that may provide them different types of support (e.g., guidance and information emotional, and academic) throughout the year. Schwartz et al () investigation of a YIM intervention found improved attitudes and behaviors in seeking support in college among first‐generation college students as well as closer relationships with their course instructors. It is important to highlight that the burden should not always be placed on students, but on college administration, faculty and staff by making their campus more welcoming and approachable, particularly for underrepresented college students; in particular, training could be offered to faculty, staff, and advanced students on how to reach out to first‐year students and support them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a combination of co‐curricular instruction, group activities and experiential assignments, participants can be oriented to explore their new social and academic environment, purposely looking into recruiting a diverse group of individuals (e.g., advanced peers, faculty, and university staff) that may provide them different types of support (e.g., guidance and information emotional, and academic) throughout the year. Schwartz et al () investigation of a YIM intervention found improved attitudes and behaviors in seeking support in college among first‐generation college students as well as closer relationships with their course instructors. It is important to highlight that the burden should not always be placed on students, but on college administration, faculty and staff by making their campus more welcoming and approachable, particularly for underrepresented college students; in particular, training could be offered to faculty, staff, and advanced students on how to reach out to first‐year students and support them.…”
Section: Discussionmentioning
confidence: 99%
“…Given that help‐seeking behaviors predict students’ development of new NMRs on their college campus, interventions should focus on teaching students how to seek support and find others for guidance as they deal with the typical stressors associated with the transition to college. Youth‐initiated mentoring (YIM) is an innovative intervention that may promote college adjustment and enhance college retention (Schwartz et al, ), in which students are taught networking and help‐seeking skills to identify and recruit mentors from their social networks (Schwartz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing has long been an advocate in addressing injustice. There has been greater emphasis in recent years on providing higher education opportunities to underrepresented and minority groups, 19 along with a growing body of literature that supports the call for colleges/universities to utilize comprehensive measures of determining applicant suitability. However, despite recognition that current quantitative measures of evaluating student performance (eg, American College Testing and Scholastic Aptitude Test) are flawed, many institutions cling to inherently biased admission practices.…”
Section: Holistic Admission Reviewmentioning
confidence: 99%
“…Indeed, higher quality mentoring relationships are associated with improved relationships with other adults [ 31 , 32 ]. Moreover, in a qualitative study [ 33 ] youth reported they felt more comfortable seeking help after participation in a mentoring program, suggesting a link between mentoring relationships and social resourcefulness. Social resourcefulness is, in turn, related to positive treatment outcomes, such as increased self-esteem, prosocial behaviors, and reductions in misconduct [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%